Adaptive multivariate double sampling and variable sampling interval Hotelling's T 2 charts - Khatun, Mahfuza; Khoo, Michael Boon Chong; Yeong, Wai Chung; Teoh, Wei Lin; Chong, Zhi Lin (Wiley, 2018)
In this article, two adaptive multivariate charts, which combine the double sampling (DS) and variable sampling interval (VSI) features, called the adaptive multivariate double sampling variable sampling interval T 2 (AMDSVSI T 2 ) and the adaptive multivariate double sampling variable sampling interval combined T 2 (AMDSVSIC T 2 ) charts, are proposed. The real purpose of using the proposed charts is to provide flexibility by enabling the sampling interval length of the DS T 2 chart to be varied so that the chart's sensitivity can be enhanced. The fundamental difference between the two proposed charts is that when a second sample is taken, the AMDSVSI T 2 chart uses the information of the combined sample mean vectors while the AMDSVSIC T 2 chart uses the information of the combined T 2 statistics, in deciding about the process status. This research is motivated by existing combined DS (Formula presented.) and VSI (Formula presented.) charts in the literature, which show convincing performance improvement over the standard DS (Formula presented.) chart. Consequently, it is believed that adopting this existing approach in the multivariate case will enable superior multivariate DS charts to be proposed. Numerical results show that the proposed charts outperform the existing standard T 2 and other adaptive multivariate charts, in detecting shifts in the mean vector, for the zero-state and steady-state cases. The performances of both charts when the shift sizes in the mean vector are unknown are also measured. The application of the AMDSVSI T 2 chart is illustrated with an example.